A thermally and mechanically stable solar cell made of a small-molecule donor and a polymer acceptor. Issue 30 (25th July 2017) - Oh, Sora; Badgujar, Sachin; Kim, Da Hun; Lee, Wang-Eun; Khan, Nasir; Jahandar, Muhammad; Rasool, Shafket; Song, Chang Eun; Lee, Hang Ken; Shin, Won Suk; Lee, Jong-Cheol; Moon, Sang-Jin; et al.
Abstract : Highly efficient and stable BDT2TR:PNDI-2T organic solar cells are investigated. Although this system shows a PCE of 4.43%, significant enhancements are observed in the thermal stability, high thickness tolerance, and flexibility as compared with the PC71 BM-based organic solar cells. Abstract : We performed systematic experiments based on a small molecule donor and a polymer acceptor containing a naphthalene diimide (NDI)-based polymer as compared with fullerene-based acceptor (PC71 BM) solar cells. Among polymer acceptors, the NDI-based polymer (PNDI-2T) shows good properties such as broad light absorbance with a strong absorption co-efficient and a well oriented crystalline structure leading to high electron mobility. We monitored the photovoltaic properties of both PNDI-2T and PC71 BM acceptors with a BDT2TR donor. Although the BDT2TR:PC71 BM device showed a higher PCE of 8.20%, the BDT2TR:PNDI-2T device also showed remarkable photovoltaic results with a PCE of 4.43%, V OC of 0.86 V, J SC of 7.26 mA cm −2, and FF of 71% indicating one of the highest efficiencies for small molecule donor and non-fullerene polymer acceptor systems. In particular, the PNDI-2T acceptor showed excellent thermal stability and intrinsic mechanical performance as compared with the PC71 BM acceptor. To demonstrate the potential of the polymer acceptor for solar devices, we fabricated a device for testing thermal stability, high thickness tolerance, and the flexibility of the solar cell with bending stress. As a result, the PNDI-2T-based solar cell exhibited excellent thermal stability at 150 °C for 15 h and the PCE of the BDT2TR:PNDI-2T device with a thick active layer (around 610 nm) maintained 80% of its initial value. Moreover, the flexible device with the BDT2TR:PNDI-2T system retained its homogeneous morphology and showed maintained photovoltaic performance even after 100 bending cycles. Therefore, PNDI-2T based organic solar cells have good potential for application as flexible and portable real energy generators.